Tracking Changes in Frontal Lobe Hemodynamic Response in Individual Adults With Developmental Language Disorder Following HD tDCS Enhanced Phonological Working Memory Training: An fNIRS Feasibility Study - Berglund-Barraza, Amy; Tian, Fenghua; Basak, Chandramallika; Hart, John; Evans, Julia L. (Frontiers in Human Neuroscience, 2020)
Background Current research suggests a neurobiological marker of developmental language disorder (DLD) in adolescents and young adults may be an atypical neural profile coupled with behavioral performance that overlaps with that of normal controls. Although many imaging techniques are not suitable for the study of speech and language processing in DLD, fNIRS may be a viable option. In this study we asked if fNIRS can be used to identify atypical cortical activation patterns in individual adults with DLD and track potential changes in cortical activation patterns following a phonological working memory training protocol enhanced with anodal HD tDCS stimulation to the presupplementary motor area (preSMA). Objective/Hypothesis The purpose of this study was two-fold: (1) to determine if fNIRS can be used to identify atypical hemodynamic responses in individual young adults with DLD during active spoken word processing and, (2) to determine if fNIRS can detect changes in hemodynamic response in these same adults with DLD following anodal HD tDCS enhanced phonological working memory training. Methods Two adult subjects with DLD (female, age 25) completed a total of two sessions of fNIRs working memory task prior to and following one session of a nonword repetition task paired with anodal HD tDCS (1.0 mA tDCS; 20 min) to the preSMA. Standardized z-scores of behavioral measures (accuracy and reaction time) and changes in hemodynamic response during an n-back working memory task for the two participants with DLD was compared to that of a normative sample of 21 age- and gender- matched normal controls (ages 18-25) prior to and following phonological working memory training. Results Individual standardized z-scores for each participant with DLD indicated that prior to training, hemoglobin response in the prefrontal lobe for both participants was markedly different from each other and normal controls. Following training, standard scores showed that the hemodynamic response for both participants moved within normal limits for ROIs. Conclusion These findings highlight the feasibility of fNIRS to establish individual differences in the link between behavior and neural patterns in single subjects with DLD, as well as track individual differences in changes in brain activity following working memory training.